Design and Build a Web-Based Budget Planning Application at Mythworx Surabaya Event Organizer - Septian, Jerry; Soebijono, Tony; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Business processes in the Event Organizer, has several things that must be done. From the process of learning data by marketing, then admin to finance for the budget. The problem that occurs is when the Event budget planning process exceeds the budget that has been budgeted. In addition, if there are changes that occur, the Event will find it difficult to immediately adjust the planned budget. This happened because it was caused by input errors and difficulty finding event data or vendor data recorded in several files. If any more processes occur, it can hamper the budget planning process. The solution offered is to create an Event budget application. this application using SDLC (System Development Life Cycle), which consists of 4 stages, Communication, Planning, Modeling and Construction. This application has a search for Event data that has been made by marketing, then the admin makes a budget, and the finance validates the budget that has been made. The results obtained are in the form of an Event budget planning system that can help the marketing, admin, and finance for the event budgeting process with consumers. The calculations for the cost budget have been tested and produce the desired output calculations